Tecto-cerebellar Dysraphism with Occipital Encephalocele: Not a Distinct Disorder, but Part of the Joubert Syndrome Spectrum? - Poretti, A.; Singhi, S.; Huisman, T.A.G M.; Meoded, A.; Jallo, G.; Ozturk, A.; Boltshauser, E.; Tekes, A. (Neuropediatrics, 2011)
Magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI) findings in a 4-year-old child with occipital encephalocele, cerebellar vermis hypogenesis, and tectal malformation are presented. The neuroimaging findings are reminiscent of tectocerebellar dysraphism with an occipital encephalocele (TCD-OE). Additionally, elongated, thickened, and horizontally orientated superior cerebellar peduncles, an abnormally deepened interpeduncular fossa, subependymal heterotopia, and focal cortical dysplasia were noted. Color-coded fractional anisotropy (FA) maps revealed an absence of the decussation of the superior cerebellar peduncles. These findings are highly suggestive of Joubert syndrome and related disorders (JSRD). Our report and the review of the published cases suggest that TCD-OE is not a nosological entity, but may represent the structural manifestation of heterogeneous disorders such as the JSRD spectrum. DTI may be very helpful to differentiate between similar midbrain-hindbrain malformations.
Keywords: cerebellar malformation; magnetic resonance imaging; diffusion tensor imaging